How does correctional institution restore the sense of humanism to criminals? Bagaimana cara lembaga pemasyarakatan mengembalikan rasa humanisme kepada koruptor? - Muhammad Miftakhuddin Hanif (Indonesian Journal of Police Studies, 2021)
Prison sentence is a form of punishment which until now is one of the favorite punishments implemented and applied in the Indonesian punishment system. Imprisonment of the existing imprisonment proved to have a lot of gap abuse in him both by wardens or by inmates even by third parties. This in fact makes the prison yag should be the place to make the deterrent effect seems to change a lot. Even those changes made prisons a fertile ground for the inmates and made the prison a place of business. Therefore, it is necessary to solve the problem and find a way out to overcome the problem to create law that is safe and prosperous and revive the sense of a deterrent effect to inmates in prisons. This research tries to examine how the correctional institution in Indonesia provide sufficient facilities for character building of prisoners to be ready to return to society. The research found that the deterrent effect of criminals is not the main goal in the pattern of abusing prisoners in various correctional institutions in Indonesia, but rather how to build the character of the prisoners so that they are accepted back into society. This research also found that, the obstacles faced in the form of inadequate institutional facilities, overcapacity in almost all prisons, and the still large number of bribes in the institutions became an ineffective coaching pattern.